.AZV Design Works Vol.03 2024 - Mahmud, Hj. Shahril Anwar; Zolkefli, Megat Faridrullah; Ahmad, Ts. Afiqah; Jamel, Nurul Shafinaz; Mos, Ar. IDr. Mitchell Tony; Sebri, Nur Izzati; Hashim, Mohd Iqbal (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Department of Architecture Kota Samarahan was established in the year 2014, currently running the undergraduate programme of Bachelor of Science (Hons.) Architecture [LAM Part 1] which prepares students in obtaining first degree qualifications. Professionally acredited by the Board of Architects Malaysia, the course emphasizes on the importance of students’ responsiveness towards the environment, in addition to the scientific and technological approach of the curricular. The holistic training approach ensures well-rounded and responsible graduates who would uphold ethics in their career alongside taking due care of the needs of the present and future generations.